Perceptions of corporate social responsibility and its influence on customer behaviour in White City, Saldanha - Nkwanyana, Nqobizizwe Agostina (Stellenbosch : Stellenbosch University, 2020)
Thesis (MMil)--Stellenbosch University, 2020.